A study of laser-induced incandescence under high vacuum conditions - Beyer, Vivien (Cranfield University, 2006)
Laser-Induced Incandescence (LII) occurs when a high-energy pulsed laser beam encounters graphitic particulate matter particles like soot or carbon black. The particles absorb laser energy from the beam and see an increase in their internal energy, resulting in an increase of temperature. At the same time, the particles loose energy through heat transfer mechanisms. If the energy absorption rate is sufficiently high, particle temperature will rise to levels where significant incandescence (blackbody emission) can occur .Typically, Laser-Induced Incandescence produces 50ns to 1μs long light pulses at atmospheric pressure. So far, LII measurements had been restrained to conduction-dominated conditions, whereby signals are short-lived (less than one microsecond) and require sensitive nanosecond resolution instrumentation. This thesis introduces a novel LII – based measurement method performed under high vacuum conditions. The novelty of LII under vacuum resided in the fact that heat conduction away from the soot particle becomes negligible below 10-2 mbar and this constituted a step away from the typical situation, whereby laser absorption is followed by heat conduction from the particles to the surrounding medium. Instead, sublimation and radiative heat transfer would follow laser absorption. The consequence was the obtention of long-lived LII signals (up to 100 microseconds) and a large gain of photons (ranging between 50 to 300) emitted per primary soot particle during LII temperature decays. Furthermore, the refractive index function E(m) value could be determined directly from measured radiative temperature decays, with potentially an uncertainty of circa 7%, which outperformed current soot extinction measurements. In addition, for laser fluences below 0.06 J/cm2, a regime where only laser energy absorption and radiative heat transfer apply would be reached and LII signals became independent of particle size. Throughout this project, Laser-Induced Incandescence under vacuum was applied to a sample of carbon powder (agglomerated soot particles) sealed in a glass vessel and held below 10-3 mbar. Initial spectral measurements performed at a laser fluence of 0.3 J/cm2 confirmed the obtention of long-lived (60 microseconds long) blackbody spectra, which confirmed the feasibility of the technique and yielded an E(m) measurement of between 0.35 and 0.45. A second study was performed with a dualwavelength pyrometric system specifically designed for recording live LII temperatures and signal intensities coupled to an absolute light intensity calibrated intensified imaging system. Experimental results unveiled the thermo-physical behaviours of agglomerates enduring LII. The most remarkable outcomes of the results concerning carbon nanoparticles agglomerates were that: clusterous particulate matter absorbs and radiates light in a very similarly to single isolated carbon nanoparticles and therefore obey largely the Rayleigh limit; soot agglomerates also dissociate during LII in an explosive mode and ejecta were measured to reach up to 400 m/s following chain dissociations; complete agglomerate dissociations can be obtained and measurements performed on individual aggregates of primary soot nanoparticles. In parallel, LII measurements revealed that optical shielding is largely present within agglomerates, and therefore clusters dissociations exposed large quantities of particulate matter and increased greatly LII signal levels. Overall, radiative heat transfer measurements yielded E(m) = 0.4 to 0.6 and time-integrated ICCD measurements resolved signal levels as low as groups of 6 carbon nanoparticles. This sensitivity clearly was the highest recorded to date for Laser Induced Incandescence and the sensitivity boundary of the technique was increased to nearly resolving single nanoparticles. Further measurements were performed in collaboration with the National Research Council (NRC) of Ottawa, Canada, at the Combustion Research Group facility. The results obtained validated the obtention of repeatable temperature profiles for Laser- Induced Incandescence under vacuum. In addition, comparison between results obtained on a controlled source of agglomerates at atmospheric pressure established that the increase for LII signals with laser fluence for both atmospheric and vacuum conditions could be directly associated with agglomerates dissociations. Indeed, net diminutions in optical shielding were measured in both conditions and could be coupled with diminutions in thermal shielding at atmospheric pressures. Highresolution temperature measurements established that laser absorption, annealing, sublimation and radiative heat transfer rates could be unprecedently and directly measured by laser-induced incandescence under vacuum. Annealing and sublimation of soot primary particles could also reasonably be assumed to be the phenomena at the heart of agglomerate dissociations. It was also established that agglomerate dissociation was dependent not only on laser fluence but also on the instantaneous laser power absorbed by the carbon agglomerates: indeed measurements performed at NRC were effected with a instantaneous laser powers four times lower than previously and radiative heat transfer measurements attested incomplete agglomerate dissociations with E(m) values measured between 0.8 and 1. Overall, the present work introduces LII under vacuum as a high sensitivity measurement method for particulate matter. The sensitivities obtained approached nanoparticles resolution and constitutes one of the most sensitive particulate matter measurement technique to date with real-time measurements capability. Because of the sample studied, agglomerate dynamics during LII were unveiled for the first time and explained the increase of LII signals with laser fluence as a diminution of both thermal and optical shielding. The LII under vacuum technique also proved its ability to resolve and isolate some of the key phenomena occurring during LII: laser absorption, annealing, sublimation and heat radiation.